1998
DOI: 10.1038/bjc.1998.178
|View full text |Cite
|
Sign up to set email alerts
|

The role of transforming growth factor alpha production and ErbB-2 overexpression in induction of tumorigenicity of lung epithelial cells

Abstract: Summary Over-expression of erbB-2 is associated with shortened survival of patients with lung adenocarcinomas. We demonstrated that human lung epithelial cells, overexpressing erbB-2, formed tumours in nude mice only when high levels of transforming growth factor (TGF)-a were produced (E6T cells). To define the role that TGF-a production played in induction of tumorigenicity, a non-tumorigenic TGF-a-negative clone of ErbB-2 overexpressing cells (E2 cells) was transfected with an expression vector for TGF-a (E2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(32 citation statements)
references
References 20 publications
2
30
0
Order By: Relevance
“…• [179,180], as acquisition of HER2/neu overexpression follows disruption of p53 function and precedes acquisition of ras mutations [181]. Surprisingly, overexpression is associated with lower stage and grade of tumor [182].…”
Section: Lungmentioning
confidence: 99%
“…• [179,180], as acquisition of HER2/neu overexpression follows disruption of p53 function and precedes acquisition of ras mutations [181]. Surprisingly, overexpression is associated with lower stage and grade of tumor [182].…”
Section: Lungmentioning
confidence: 99%
“…We previously demonstrated the presence of constitutive ErbB-1/ErbB-2 heterodimers in tumorigenic E6T cells [13]. Since receptor dimerization is ligand-dependent [4], and determines which downstream signaling pathways will be activated [7], we examined the presence and relative abundance of ligands for ErbB-1 in both the tumorigenic E6T and the non-tumorigenic E6TA cells.…”
Section: Expression Of Erbb-1 Ligands and Hrgmentioning
confidence: 99%
“…Since receptor dimerization is ligand-dependent [4], and determines which downstream signaling pathways will be activated [7], we examined the presence and relative abundance of ligands for ErbB-1 in both the tumorigenic E6T and the non-tumorigenic E6TA cells. Earlier studies had shown that EGF is not produced by BEAS-2B or its ErbB-2-overexpressing derivatives [15], while TGFa secretion by E6T cells (243 pg/ml per 10 6 cells) was reduced by 93% (17 pg/ml per 10 6 cells) by expression of an antisense construct in E6TA cells [13]. We initially examined the mRNA expression of the ErbB-1 ligands AR and BTC by RT-PCR.…”
Section: Expression Of Erbb-1 Ligands and Hrgmentioning
confidence: 99%
See 2 more Smart Citations